Racism changing attitudes 1900-2000 - Grant, Reg (20th century issues, 1999)
The twentieth century has witnessed some of the most horrific racist acts in history. But, this book which is one of a series shows how, in many countries it has also seen far-reaching and positive progress in the field of civil rights